Penentuan Utang yang Telah Jatuh Waktu pada Click-Wrap Agreement yang Tidak Mencantumkan Klausul Jatuh Waktu Utang - Louis Alfred Hasudungan; Elisatris Gultom; Nyulistiowati Suryanti (Universitas Batanghari Jambi, 2022)
Bankcruptcy and Suspension of Payment law is a great solution for debitor who have debt problems with their creditors. Debtors can be declared bankrupt or Suspension of Payment if the debtor is simply proven to have debts to 2 (two) or more creditors and is simply proven to have